Ex-situ bioremediation of crude oil in soil, a comparative kinetic analysis - Mohajeri, L. (2010)
Weathered crude oil (WCO) removals in shoreline sediment samples were monitored for 60 days in bioremediation experimentation. Experimental modeling was carried out using statistical design of experiments. At optimum conditions maximum of 83.13, 78.06 and 69.92% WCO removals were observed for 2, 16 and 30 g/kg initial oil concentrations, respectively. Significant variations in the crude oil degradation pattern were observed with respect to oil, nutrient and microorganism contents. Crude oil bioremediation were successfully described by a firstorder kinetic model. The study indicated that the rate of hydrocarbon biodegradation increased with decrease of crude oil concentrations.